Mutagenesis of the Catalytic and Cleavage Site Residues of the Hypovirus Papain-Like Proteases p29 and p48 Reveals Alternative Processing and Contributions to Optimal Viral RNA Accumulation - Jensen, Kenneth S. (American Society for Microbiology, 2014)
The positive-stranded RNA genome of the prototypic virulence-attenuating hypovirus CHV-1/EP713 contains two open reading frames (ORF), each encoding an autocatalytic papain-like leader protease. Protease p29, derived from the N-terminal portion of ORF A, functions as a suppressor of RNA silencing, while protease p48, derived from the N-terminal portion of ORF B, is required for viral RNA replication. The catalytic and cleavage site residues required for autoproteolytic processing have been functionally mapped in vitro for both proteases but not confirmed in the infected fungal host. We report here the mutagenesis of the CHV-1/EP713 infectious cDNA clone to define the requirements for p29 and p48 cleavage and the role of autoproteolysis in the context of hypovirus replication. Mutation of the catalytic cysteine and histidine residues for either p29 or p48 was tolerated but reduced viral RNA accumulation to ca. 20 to 50% of the wild-type level. Mutation of the p29 catalytic residues caused an accumulation of unprocessed ORF A product p69. Surprisingly, the release of p48 from the ORF B-encoded polyprotein was not prevented by mutation of the p48 catalytic and cleavage site residues and was independent of p29. The results show that, while dispensable for hypovirus replication, the autocatalytic processing of the leader proteases p29 and p48 contributes to optimal virus RNA accumulation. The role of the predicted catalytic residues in autoproteolytic processing of p29 was confirmed in the infected host, while p48 was found to also undergo alternative processing independent of the encoded papain-like protease activities. IMPORTANCE Hypoviruses are positive-strand RNA mycoviruses that attenuate virulence of their pathogenic fungal hosts. The prototypic hypovirus CHV-1/EP713, which infects the chestnut bight fungus Cryphonetria parasitica, encodes two papain-like autocatalytic leader proteases, p29 and p48, that also have important functions in suppressing the RNA silencing antiviral defense response and in viral RNA replication, respectively. The mutational analyses of the CHV-1/EP713 infectious cDNA clone, reported here, define the requirements for p29 and p48 cleavage and the functional importance of autoproteolysis in the context of hypovirus replication and exposed an alternative p48 processing pathway independent of the encoded papain-like protease activities. These findings provide additional insights into hypovirus gene expression, replication, and evolution and inform ongoing efforts to engineer hypoviruses for interrogating and modulating fungal virulence.